دراسة السلوك الديناميكي للسفينة المتأرجحة عرضيّاً على الأمواج الجيبية المنتظمة - بربهان, ميشيل; علي, رامي (Latakia University Journal -Engineering Sciences Series, 2016)
تعتبر دراسة السلوك الديناميكي للسفينة المتأرجحة عرضيّاً على الأمواج من المواضيع ذات الأهمية الخاصة, وذلك نظراً لارتباطها الوثيق بأمان السفينة التوازني, وتأثيرها المباشر على كفاءة عمل بعض الأنظمة والعمليات داخل بدن السفينة. يتضمن هذا البحث شرحاً للنموذج الرياضي المقترح والخاص بدراسة السلوك الديناميكي للسفينة المتأرجحة عرضيّاً على الأمواج الجيبية المنتظمة بهدف حساب تابع الخاصية السعوية لاستجابة السفينة بفعل الموجة المحرضة على التأرجح العرضي, ومن ثمّ تحديد تردد الطنين والقيمة العظمى للخاصية السعوية. تم إعداد برنامج حاسوبي بلغة ( ) لتنفيذ الحسابات وفقاً للنموذج المقترح, مما سمح بدراسة تأثير بعض البارامترات الاستثمارية للسفينة (كسرعة السفينة, وزاوية خط سيرها بالنسبة إلى الاتجاه الرئيسي لانتشار الأمواج) على تردد الطنين والقيمة العظمى للخاصية السعوية, كما سمح أيضاً بدراسة تأثير بعض بارامترات الوسط المحيط (كتردد الموجة الجيبية) على القيمة العظمى للخاصية السعوية. تم التوصل من خلال هذا البحث إلى استخراج علاقات رياضية تسمح بوضع تفسير دقيق وواضح للسلوك الديناميكي للسفينة المتأرجحة عرضيّاً على الأمواج البحرية. The study of the dynamic behavior of the rolling ship on sea waves is one of most interesting topics, due to its close association with the ship stability and its direct impact on the efficiency of the work of some of the systems and processes inside the hull. This research includes an explanation of the proposed mathematical model to study the dynamic behavior of the rolling ship on regular sinusoidal waves in order to calculate the Transfer Function of ship response continued to the act of wave-induced transverse oscillation and thus determine the frequency of resonance and the maximum value for the Transfer Function. A computer program was prepared to perform calculations according to the proposed model, which allowed studying the effect of some parameters of the investment of the vessel (ship speed, and the angle of its route for the main direction of spread of the waves) at a frequency of resonance and the maximum value for the Transfer Function, and also allowed to study the effect of Some of the parameters of the surrounding medium (wave frequency) to the maximum value for the Transfer Function. Through this research, it had been reached to extract mathematical equation which allows a precise and clear explanation of the dynamic behavior of the ship rolling on waves.